Roles of Pharmacy, Medicine, Nursing, Laboratory, Anesthesia, Urology, Public Health, and Occupational Health, Infection Control, and Hospital Management, in the Integration of Telehealth in Saudi Arabia: A Comprehensive Review - Hanbashi, Yasser Mohammed; Alessa, Mohammed Hassan; Dighriri, Ibrahim Mohammed; Al Kulayb, Jaamil Ali Hussain; Almohamedh, Hamad Saleh Faraj; Alyami, Mutared Mohammed Mutared; Badr, Khalid Ghazi; Almufadhili, Ahmed Homoud; Al-Sulimani, Suhaib Talal; Al-Moqren, Abdullah Fawzi; Huldar, Abdullatif Adnan; Al- Ghamdi, Ali Ahmed; et al. (Journal of Ecohumanism, 2024)
Different sectors have contributed to successfully integrating telehealth services into the Saudi healthcare system during the emergent need for high-quality health services. Hence, this review attempts to assess different sectors and their professionals for their contribution toward the implementation and sustainability of telehealth services, including pharmacy, medicine, nursing, laboratory services, anesthesia, urology, public health, occupational health, infection control, and hospital management. Each sector offers a unique contribution to the emergence and continuity of telehealth services, and physicians have implemented telehealth for diagnosis while maintaining chronic patients at home with distant control. Pharmacists have started providing medication support through telehealth, and physicians have extended their use by treating chronic patients through teleconsulting. Hospital nurses have improved their professional access by providing virtual education and consulting to treat chronic patients. Laboratory services enable fast and accurate diagnosis, and anesthesiologists have begun to use it for preoperative and postoperative assessments. Urologists have integrated telehealth into the management of chronic patients. Public health professionals provide telehealth services for health promotion, disease prevention, and management. Occupational health practitioners provided remote ergonomic consultation. Infection prevention and control teams delivered training sessions and telehealth surveillance of hygiene-related practices. In addition, initiatives to plan and create a system for telehealth implementation are a significant contribution to hospital management. The incorporation of telehealth across professional silos has increased the quality-of-care delivery, enhanced patient empowerment, and built system resilience in Saudi Arabia. This multidisciplinary collaboration thus underscores how furthering telehealth services can only be realized through cooperation to ensure equitable access and advance healthcare modernization under any national initiative.